2005
DOI: 10.1108/00368790510595093
|View full text |Cite
|
Sign up to set email alerts
|

The effects of bearing distortion on the performance of hydrodynamic thrust bearings

Abstract: PurposeIn this work, the performance characteristics of thrust bearings are studied by taking into account bearing distortions.Design/methodology/approachThe pressure distribution in the bearing is found using Reynolds' equation. Reynolds' equation is solved under isothermal conditions by assuming oil viscosity constant. The amount of deformation in the bearing is determined using constitute equations applied to linear elastic materials. It is preferred to work with dimensionless equations for the result to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Consequently, it is easily observed that the maximum decrease in the load capacity for the pair of steel‐bronze is more than 50 per cent of that occurring in the pair of steel‐steel. The results of the present paper are consistent with those obtained in previous works (Rothbart, 1964; Toklar, 2003; Güllü, 2005; Wang et al , 2006), regarding the decrease in load capacity, the order of this decrease, and bearing size ratios for which the maximum decrease occurs.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Consequently, it is easily observed that the maximum decrease in the load capacity for the pair of steel‐bronze is more than 50 per cent of that occurring in the pair of steel‐steel. The results of the present paper are consistent with those obtained in previous works (Rothbart, 1964; Toklar, 2003; Güllü, 2005; Wang et al , 2006), regarding the decrease in load capacity, the order of this decrease, and bearing size ratios for which the maximum decrease occurs.…”
Section: Resultssupporting
confidence: 93%
“…Non‐dimensional loads and decrease percentages in the load capacity are given in Tables I and II, for the pairs of steel runner‐steel pad and steel runner‐bronze pad, respectively. In these tables, the results obtained in the present paper are given, for comparison purposes, along with the results presented in two previous works which consider the case of both pad and runner being rigid, and the case of deformable pad but rigid runner (Toklar, 2003; Güllü, 2005).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Hydrodynamic thrust slider bearings have been theoretically studied plentifully by considering non-Newtonian fluids, surface roughness, fluid film viscous heating and surface elastic deformation [1][2][3][4][5][6][7][8]. Those studies addressed the bearing clearances over 0.1 μm, which is normally far larger than the thickness of the physically adsorbed layer on the bearing surface.…”
Section: Introductionmentioning
confidence: 99%